Against Epistocracy. Issue 1 (2nd January 2019) - Gunn, Paul
ABSTRACT: In Against Democracy, Jason Brennan argues that public ignorance undermines the legitimacy of democracy because, to the extent that ignorant voters make bad policy choices, they harm their own and one another's interests. The solution, he thinks, is epistocracy, which would leave policy decisions largely in the hands of social-scientific experts or voters who pass tests of political knowledge. However, Brennan fails to explain why we should think that these putative experts are sufficiently knowledgeable to avoid making errors as damaging as those made by voters. Given the strong link between political knowledge and ideological dogmatism, as well as the tendency of social scientists to disagree with one another, the case for epistocracy is deeply implausible, at best. Moreover, given that there are important non-instrumental justifications of democracy—justifications of which Brennan appears to be radically ignorant—the epistocratic alternative would be unnecessary even if it were viable.